THE USE OF CODE BY THE MOSLEM SPEECH COMMUNITY OF PEGAYAMAN - Adi Jaya Putra, I Nyoman (e-Journal of Linguistics, 2009)
The research conducted in Pegayaman is a sociolinguistic study with anatural approach. Through this research, the code choice done by the Moslemspeech community of Pegayaman was intended to be uncovered. The subjects ofthe study under investigation reside in Pegayaman village of Sukasada sub-district,Buleleng, Bali. The problems are formulated as follows: 1) What code(s) are foundin this community, and which is the most dominant one to be chosen for use in theseven language domains being studied?; 2) How is the most dominantly chosencode used in their daily verbal interaction?; 3) What do they think of and say aboutthe choice of the code, and its inheritance to the following generation?; and 4) Whydo they insist on maintaining to behave verbally as such, as is indicated by theanswers to questions (1), (2), and (3)?The results of the data analysis empirically show the followings: (1)Balinese language (BL), Indonesian language (IL), and Arabic are three main codeswhich are used, and among them BL is the code that is dominantly chosen and usedto communicate verbally; (2) There is a diglossic language situation in this speechcommunity, especially when they are interacting verbally using BL; (3) There is akind of code mixing phenomenon; (4) A number of terms of address and terms ofreference found which are exclusively Pegayaman in nature; among them are Dané,Tuan and Guru; (5) Some particles like hee, see, and laa are found and mostly usedby women of older age which, sociolinguistically speaking, function as the markersof their social group identity.With regard to the use of Bahasa Bali as well as with the teaching or thepassing down of the language to the following generation, it is found out that theMoslem speech community of Pegayaman has a positive point of view. Such aview has been exemplified by the penglingsirs and also by the other informal andformal leaders of the village in appreciating and using the language. Anotherdetermining factor is the support given by the local government. The mostimportant factor among these, however, is that because the people of this Moslemspeech community identify themselves as being Balinese.The dominant use of BL in verbal interaction can be explained as anattitude that indicates an adherence of this Moslem speech community to BL. It canbe concluded that the ultimate causation of their verbal behavior (starting fromchoosing BL, using it in verbal interaction, until passing it down) is to maximizetheir fitness—to maintain their ‘Balinese’ existence. By using BL, they want toshow their identity (either social or ethnic), and their typical Balinese Moslemculture of Pegayaman. Individually or communally, this kind of identity is realizedas an important factor to maintain their existence among the communities of non-Moslem Balinese.
Keywords: code, moslem speech community of Pegayaman, sociolinguistics